2018
DOI: 10.1097/scs.0000000000004314
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Topical Application of Nigella sativa on Acute Radiation-Induced Nasal Mucositis

Abstract: The goal of this study was to demonstrate the effect of radiotherapy (RT) on nasal mucosa in rats and to evaluate the radioprotective effects of the topical application of black seed oil (Nigella sativa [NS]) to treat acute radiation-induced nasal mucositis.A total of 18 rats were randomized into 3 groups, with 6 animals per group. The rats in group 1 were topically administered saline in the nasal cavity after sham irradiation. Group 2 received saline at the same dose after irradiation. Group 3 was given NS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The volatile oil obtained from the seeds contains many constituents such as thymoquinone, carvacrol, thymol, α - and β -pinene, 4-terpineol, and nigellone, among others [20], and the therapeutic benefit of the seed extract is well characterized [21]. In this regard, Nigella sativa (NS) oil is tried in different animal models of radiation-induced mucositis because of its pleiotropic activities [22, 23] with promising pieces of evidence of successful outcomes. Accordingly, the present study aims at evaluating the effects of Nigella sativa oil as a mouth rinse against CT-induced OM in patients with acute myeloid leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…The volatile oil obtained from the seeds contains many constituents such as thymoquinone, carvacrol, thymol, α - and β -pinene, 4-terpineol, and nigellone, among others [20], and the therapeutic benefit of the seed extract is well characterized [21]. In this regard, Nigella sativa (NS) oil is tried in different animal models of radiation-induced mucositis because of its pleiotropic activities [22, 23] with promising pieces of evidence of successful outcomes. Accordingly, the present study aims at evaluating the effects of Nigella sativa oil as a mouth rinse against CT-induced OM in patients with acute myeloid leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…This result was in tune with the finding of Lotfy and Zayed that demonstrate effective attenuation of tissue damage by the use of NS oil in 5fluorouracil-induced OM in rats [32] . Moreover, Canakci et al reported that topical application of NS oil effectively prevents the superficial erosion of the RTinduced nasal mucositis in rats [33] . Radiation-induced OM is one of the most reported complications of RT that impairs the patient's quality of life with consequent attempts to reduce the dose of radiation and treatment termination [34,35] .…”
Section: Discussionmentioning
confidence: 99%
“…Thymoquinone, as indicated by diverse laboratory investigations (Gawron et al, 2019 ; Goel & Mishra, 2018 ; Kouidhi et al, 2011 ; Mouwakeh et al, 2019 ; Randhawa et al, 2015 ), exhibits both antifungal and antibacterial attributes, thus eliminating the need for supplementary antifungal medications. Moreover, some animal investigations have explored the histopathology of wound healing involving N. sativa , revealing encouraging findings (Al‐Douri & Al‐kazaz, 2010 ; Çanakci et al, 2018 ). However, as the clinical confirmation of the antifungal properties of N. sativa is pending, the authors opted for ethical considerations and prescribed nystatin for both groups.…”
Section: Discussionmentioning
confidence: 99%